Bagaimana Anak Muda Memahami Kesenjangan Ekonomi? - Victorius Didik Suryo Hartoko; Thomas Dicky Hastjarjo; Avin Fadilla Helmi (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This study aimed to find out how young adult understand the economic disparity issue and whether ideas related to that problem had authoritarianism and materialism inclinations. The study was done to a group of university students age 18 – 30 years old. There were 295 people participating in the study. It utilized a survey with an open-ended questionnaire to figure out participants’ feelings and thoughts toward economic disparity. Subjects also filled out authoritarianism and materialism scales. The result showed that subjects’ responses toward economic disparity could be categorized into three types: 1) critical response (structural), 2) naive individualistic response and 3) fatalistic response. Most subjects provided a naive individualistic response. Result of the cross-tabulation test showed that authoritarianism had a negative correlation with a critical response but had a positive correlation with naive individualistic response. Materialism had a positive correlation with naive individualistic response. Authorianism and materialism were not related to a fatalistic response.